Deliberate Self-harm among Young People Begins to Increase at the Very Early Age: a Nationwide Study - Jung, Kwang Yul; Kim, Taerim; Hwang, Sung Yeon; Lee, Tae Rim; Yoon, Hee; Shin, Tae Gun; Sim, Min Seob; Cha, Won Chul; Jeon, Hong Jin (Journal of Korean medical science, 2018)
Suicide in young people is one of most common cause of death; and deliberate self-harm (DSH) is important indicator of suicide. It is currently unclear how old the rate begins to increase or when it reaches to the same level with adults. The purpose of this study was to find beginning age of DSH and compare their characteristics with adults. This study retrospectively reviewed 5 years of nationwide prospective registry named Emergency Department-based Injury In-depth Surveillance (EDIIS) registry composed of all injured patients who were admitted to twenty tertiary university hospital emergency departments. Injured patients aged 29 years or younger from January 1, 2011 to December 31, 2015 were included. Incidence rate of DSH in all age was described. Patients were stratified by age: early teenage (11-15 years), late teenage (16-19 years), and early adulthood (20-29 years). Data of early teenage group were compared to those of other groups for examining their characteristics. Among 588,549 injury patients, 8,400 patients reported DSH. The rate began to rise at age 11 and reach at age 16 which was equivalent to that of age 20 to 29. Early teenage had significantly higher excess mortality ratio based injury severity score (EMR-ISS) and had almost same level without significant difference in operation incidence or mortality compared to late teenage and early adulthood. DSH rate began to rise at age 11, reaching adulthood level at age 16 in Korea.